Induction of Gene Amplification Contribute to Sulfonamide Resistance in Proteus mirabilis - Zeerak Abdulrahman (College of Education for Pure Sciences, 2007)
Thirty Isolates of Proteus mirabilis from different clinical sources (Urine, Bum, Ear, and Wounds) were recovered. All isolates were subjected to the series of confirming tests to insure that these isolates are Proteus mirabilis, which identified selectively by unique feature of morphological, cultural, and biochemical tests. Amplification of plasmid DNA content (Copy Numbers), performed using 150 ~g /ml chloramphenicol and tetracycline (The chosen isolates were resistant to chloramphenicol and tetracycline, but sensitive to trimethoprim) separately in the lag phase of the tested bacterial isolates. Among seven tested isolates true amplification perceived in isolate No. 2, 8, and 10 for Chloramphenicol and isolate No. 1 and 11 for tetracycline. When cells of Proteus mirabilis cultured in medium containing chloramphenicol at 150 ~g /ml a growth lag of 20 hrs ensure. During this lag, chloramphenicol induces selective amplification, including the gene for resistance to sulfonamide. This result suggests that amplified DNA contained genes that contributed to sulfonamide resistance when present in greater amount compared with non-amplified DNA. This mechanism represents a new level of control of gene expression in bacterial system- namely, the induction of selective gene amplification.